Explanatory model of psychosis: impact on perception of self-stigma by patients in three sub-saharan African cities (2016)
Mental disorders are cross-culturally ubiquitous [1]. Psychosis is, by far, the more easily recognisable form of mental disorder by the lay public and traditional healers [2]. While the experience of psychosis is universal, interpretation of the experience, notions of causation, treatment, preferred source of care, and the consequences and perceptions of associated stigma vary from one culture to another. We used a mixed-methods approach consisting of in-depth interviews with key informants to explore respondents’ explanatory models of the causation of psychosis as well as questionnaire assessment of the level of internalized (or self) stigma. The conduct of the interviews was guided by the specifications of the McGill Illness Narrative Interview (MINI) [32], a semi-structured interview guide which, among other things, elicits lay illness narratives. A purposively selected sample of patients who were receiving treatment from traditional healers was interviewed. The transcribed interviews were read several times by the first author and subjected to thematic analysis. Supernatural and biopsychosocial explanatory models of the causation of psychosis were both endorsed by our respondents. Despite this, the majority of the respondents with severe forms of self-stigma held supernatural attributions. However, we also found that some respondents with low self-stigma embraced a supernatural model while some respondents with high self-stigma proffered a biopsychosocial explanation. Our findings suggest that individualising interventions to minimize self-stigma may be a better approach than programs that generically promote biopsychosocial models or discourage supernatural models.